Leading Equitable Teaching and Learning: Principal Lessons Learned about Instructional Clarity and Coherence - Brad W. Kose PhD (Educational Considerations, 2025)
Although greater instructional coherence is associated with improved teaching and learning, the empirical evidence on leadership practices that build instructional coherence remains limited. This article explores the experiences of a school principal returning to K-12 education with a focus on leading for equitable teaching and learning. The author analyzes and shares lessons learned about promoting equitable instructional coherence. The findings offer important implications for leadership practice, preparation, and scholarship.
Keywords: instructional leadership; instructional coherence; leadership for equity